Nature and the Singapore Resident - Yuen, Belinda K. P. (Institutional Knowledge at Singapore Management University, 1999)
Singapore has witnessed rapid urban development in the last thirty years. Its landscape has changed from one of slums and squatters in the immediate post-war years to a city of gardens and high-rise high-density housing. The concept of a 'garden city' was introduced to guide the development of a city-state with abundant greenery. In the process, many parks and gardens were created including park connectors which are green linkages between parks and other land uses, This paper presents the findings of an ongoing research into park connectors. It reports on that part of the survey results which examine the views of residents towards nature provision in park connectors and suggest some design options to enhance the planning of park connectors.